2020
DOI: 10.1002/wps.20692
|View full text |Cite
|
Sign up to set email alerts
|

Economics and mental health: the current scenario

Abstract: Economics and mental health are intertwined. Apart from the accumulating evidence of the huge economic impacts of mental ill‐health, and the growing recognition of the effects that economic circumstances can exert on mental health, governments and other budget‐holders are putting increasing emphasis on economic data to support their decisions. Here we consider how economic evaluation (including cost‐effectiveness analysis, cost‐utility analysis and related techniques) can contribute evidence to inform the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
227
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(236 citation statements)
references
References 78 publications
8
227
0
1
Order By: Relevance
“…typhoon eye effect might be due to socio-economic burden on the families due to lockdown in the country. As studies have shown that financial constraints or economic hardships not only increased behavioral problems but also damaged the physical and mental health status of individuals and their families [37]. Thus, our findings identify family size as a critical contingency factor in the prediction of typhoon eye effect and ripple effect.…”
Section: Discussionsupporting
confidence: 57%
“…typhoon eye effect might be due to socio-economic burden on the families due to lockdown in the country. As studies have shown that financial constraints or economic hardships not only increased behavioral problems but also damaged the physical and mental health status of individuals and their families [37]. Thus, our findings identify family size as a critical contingency factor in the prediction of typhoon eye effect and ripple effect.…”
Section: Discussionsupporting
confidence: 57%
“…However, relatively few studies have examined the healthcare costs associated with internet-delivered PMPs, or formally explored their cost-effectiveness 22,29 . Economic evaluations of new interventions are essential to inform decision makers about the relative value of new interventions, and for informing health service planning, viability and scalability 19,26 . To our knowledge, only one study (n = 140) has formally examined the costeffectiveness of an internet-delivered pain management intervention 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan, we focused on family size, and the possible explanation for family size to reverse the effect of the ripple effect vs. typhoon eye effect might be due to socio-economic burden on the families due to lockdown in the country. As studies have shown that nancial constraints or economic hardships not only increased behavioral problems but also damaged the physical and mental health status of individuals and their families [37]. Thus, our ndings identify family size as a critical contingency factor in the prediction of typhoon eye effect and ripple effect.…”
Section: Discussionmentioning
confidence: 49%